CORRELATION OF HAEMOGLOBIN LEVEL WITH INTESTINAL PARASITES IN SCHOOL CHILDREN OF PESHAWAR UNIVERSITY - Khan, Mir Hassan; Azim, Attia; Banuri, Faiza; Mabood, Neelum; Ali, Zardad (Journal of Ayub Medical College Abbottabad, 1993)
Parasitic infection and Hb level of 230 school children at Peshawar University were observed during October, 1992 to May, 1993. The overall infection rate was 29.1% of which 6% showed mixed infection. Among positive eases Ascaris lumbricoids was the commonest (38.8%), followed by Hymenolepis nana (26.9%). E. Coli was present in 10.4% cases, G. Lambliain 9% cases and E. Histolytica in 6% cases. However, the prevalence rale each for T. Saginate and E. Vermiculeris was 3%, while T. Trichiure and Hookworm each was found in 1.5% eases. The mean haemoglobin in healthy subject was 13.6 g/dl, while in infected subjects it was 11.4 g/dl. the difference was statistically significant (P<0.05).